STRATEGI PENINGKATAN KINERJA UMKM PRODUK MINUMAN MR. ONE CABANG TUASAN BERDASARKAN NILAI-NILAI MANAJEMEN ISLAM - Zainarti Zainarti; Adelia Natasya; Luthfi Hafiz; Riski Nita Maulina Putri Tambak (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to analyze strategies for improving the performance of Mr. Beverage Products Umkm. One Tuasan Branch is based on Islamic management values. This research seeks to identify and test the effectiveness of implementing values ​​such as honesty, justice, trustworthiness and sharia in the context of MSME management and operations. This research uses a qualitative approach with a case study method, which was chosen because it was considered appropriate to examine in depth the application of Islamic management values ​​in improving the performance of Mr. Beverage Products Umkm. One Tuasan Branch. The research location is the MSME Beverage Products Mr. One Tuasan Branch located on Jl. Tuasan No.. 80, Sidorejo Hilir, Kec. Medan Tembung, Medan City, North Sumatra. The research time will be determined based on agreement with the Umkm and considering the time needed to collect sufficient and in-depth data. Research data will be obtained from two main sources: observation and interviews. Based on the results of this research, it can be concluded that the application of Islamic values ​​in the management and operations of Mr. Beverage Products Umkm. One Tuasan Branch has had a significant positive impact. Values ​​such as honesty, fairness, trust, and sharia not only support the success of daily operations, but also strengthen Mr.